Communication practices and information exchange for caregivers of children with cancer in Pakistan - Graetz, Dylan E.; Wardell, Joseph; Hameed, Ambreen; tul Quanita, Afia; Najmi, Atoofa; Ahmad, Safwan; Shafiq, Muhammad; Naheed, Asma; Munir, Shabnam; Ferrara, Gia; Staples, Courtney; Chen, Yichen; et al. (Frontiers in Oncology, 2025)
IntroductionInformation exchange is a core component of communication that has been understudied globally. This study sought to examine eight core functions of communication, including information exchange, among caregivers of children with cancer in Pakistan, a middle-income country with >8,000 new cases of childhood cancer each year.MethodsA cross-sectional survey was administered to 200 caregivers of children with cancer at two major centers in Pakistan. Surveys contained socio-demographic characteristics and questions related to priorities and experiences for communication and information exchange. Surveys were verbally administered from March-November 2023.ResultsWhile over 90% of caregivers prioritized all eight functions of pediatric cancer communication, significantly fewer (p<0.001) experienced each function. Caregivers wanted to know likelihood of cure (99.5%) and late effects (97%), but how they wanted to receive information varied. Most caregivers (>90%) understood what type of treatment their children would receive; fewer correctly identified diagnosis (77%), location (81%), or treatment duration (71%). Caregivers of patients with leukemia were more likely to have a complete understanding of their child’s diagnosis and treatment (p<0.0001).ConclusionPakistani caregivers express many of the same communication needs noted in other settings, with similar challenges and larger gaps in care. Interventional work should focus on maximizing human resources, ensuring complete information exchange, and empowering caregivers.